PERSEPSI MASYARAKAT TERHADAP PERMAINAN KOA DI JORONG KOTO PANJANG KANAGARIAN KAMANG HILIR KABUPATEN AGAM - Rahman Hidayat; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The koa game is a popular game in Kamang Hilir sub-district, especially in Koto Panjang village. Koa games are a wealth of local culture that should be used in learning about nature and encourage the growth of social interaction in society. This game is usually performed by men.s minang to fill spare time or an event to gather together and sometimes this game is also played when there are traditional events in one area in Minangkabau. The rules in the koa game also contain ethics that are carried out in Minangkabau, one example is prohibited from using the left hand in playing koa . This is because in Minangkabau cultural customs, using the left hand to interact with other people is considered impolite. Koa games are often associated with the community as gambling. This is caused by several parties who take advantage of this game for negative things. Resulting in the emergence of views or perceptions among the public that the game of koa is part of gambling. The theory used in this study is the theory of perception. This research is a descriptive quantitative research. The population of this study were all communities in  Koto Panjang village, while the sample in this study was 75% of the total population. Data collection was carried out by observation, preparing a list of questions or questionnaires, and documentation. The results of this study can be concluded that the public perception of the koa game in Jorong Koto Panjang is a positive perception. Meanwhile, the factors that influence it are the recipient factor, the situation factor, and the object factor.  Keywords: Perception, The Traditional Game Of Koa